Advances in hospitality and leisure. Vol. 2 - Chen, Joseph S. (Advances in hospitality and leisure,, 2006)
Advances in Hospitality and Leisure, a peer-review journal published annually, delivers refreshing insights of a host of scientific studies pertaining to hospitality, leisure, and tourism, while providing a forum to stimulate discussions on contemporary issues and emerging trends essential to theory advancement, as well as professional practices from a global perspective. The main focus of the series is to divulge the innovative methods of inquiry, so as to inspire new research topics that are vital and have been in large neglected. The series attempts to address the needs of the populace willing to disseminating seminal ideas, concepts and theories derived from scholarly investigations. Potential readers may retrieve useful texts helping outline new research agendas, suggest viable topics for a dissertation work, and augment the knowledge of the new subjects of learning.